Analysis Positioning Mobile Banking According to Community Perception in Indonesia Based on Perceived Usefulness, Perceived Ease of Use, Security and Trust (Case Study on Mobile Banking BCA, BRI, BNI, Mandiri) - Bela Puspita Dewi; Ama Suyanto (Budapest International Research and Critics University, 2022)
At this time technology continues to develop to be more sophisticated with the presence of the internet. One of the technologies in mobile banking services. Along with the increasing number of mobile banking transactions in Indonesia, on the other hand, there is competitive competition between BCA Mobile, BRI Mobile, BNI Mobile Banking and Livin' by Mandiri which presents features that are not much different. The purpose of this study is to describe the positioning of the four mobile banking services and to find out which mobile banking is the most superior based on perceived usefulness, perceived ease of use, security and trust. The research method used is a quantitative method with descriptive analysis techniques and Multidimensional Scaling (MDS). This research uses non-probability sampling technique. The data used is primary data by distributing questionnaires with a total of 385 respondents. The results showed that BCA Mobile was ranked first in terms of perceived usefulness, perceived ease of use, security and trust. Then Livin' by Mandiri was ranked second, after that the third place was BRI Mobile and in fourth place was BNI Mobile Banking.